Development and Prospects of Triboelectric Nanogenerators in Sports and Physical State Monitoring - Zhang, Jingshui; Yang, Zhou; Liang , Xin (Frontiers in Materials, 2022)
Sports and physical fitness play important roles in people’s daily life. By sticking to exercise we can better enjoy a healthy life. Scientific and accurate monitoring of sports training and individual physical condition is important. However, many challenges still need to be solved, such as the complex design of measurement devices, the external power supplies, inaccurate measurement data, and unscientific measurement methods. Recently, the TENG-based self-powered real-time measurement sensors have attracted much more attention due to their unique advantages such as wearable features, simple construction, a wide choice of materials, and operation without external power supply. They can measure a wide range of real-time data such as haptics, velocity, pressure, and dynamic movement. In addition, they can also be made into a human–machine interactive device to provide athletes with a scientific approach to training. In this review, the working principle of TENGs is summarized and clarified. Moreover, the applications of the TENG in the areas of tactical strategy in sports, individual sports training, and physical state monitoring are also reviewed. Finally, the challenges and development opportunities faced by the TENG are also discussed and summarized.